2017
DOI: 10.1371/journal.pone.0184183
|View full text |Cite
|
Sign up to set email alerts
|

Sugar analog synthesis by in vitro biocatalytic cascade: A comparison of alternative enzyme complements for dihydroxyacetone phosphate production as a precursor to rare chiral sugar synthesis

Abstract: Carbon-carbon bond formation is one of the most challenging reactions in synthetic organic chemistry, and aldol reactions catalysed by dihydroxyacetone phosphate-dependent aldolases provide a powerful biocatalytic tool for combining C-C bond formation with the generation of two new stereo-centres, with access to all four possible stereoisomers of a compound. Dihydroxyacetone phosphate (DHAP) is unstable so the provision of DHAP for DHAP-dependent aldolases in biocatalytic processes remains complicated. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Prior comparison of enzymes that could be used for the first two steps of the model synthesis 18 had suggested that the most suitable enzymes for glycerol phosphorylation were a Thermococcus kodakarensis glycerol kinase (GlpK Tk ) and a Mycobacterium smegmatis acetate kinase (AceK Ms ). For the NAD + -dependent production of DHAP from glycerol-3-phosphate (G3P), E. coli glycerol-3-phosphate dehydrogenase (G3PD Ec ) and the water-forming NADH oxidase from Clostridium aminovalericum (NOX Ca ) were selected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior comparison of enzymes that could be used for the first two steps of the model synthesis 18 had suggested that the most suitable enzymes for glycerol phosphorylation were a Thermococcus kodakarensis glycerol kinase (GlpK Tk ) and a Mycobacterium smegmatis acetate kinase (AceK Ms ). For the NAD + -dependent production of DHAP from glycerol-3-phosphate (G3P), E. coli glycerol-3-phosphate dehydrogenase (G3PD Ec ) and the water-forming NADH oxidase from Clostridium aminovalericum (NOX Ca ) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…The pAF1 vector that encodes the DHAP-dependent fructose-1,6-biphosphate aldolase from Staphylococcus carnosus was a gift from Dr A. Frazer (University of Manchester, Manchester, UK). For all other constructs, the gene of interest was sourced as described previously 25 , codon-optimized for expression in E. coli and synthesized by GeneArt (ThermoFisher Scientific, Germany), then cloned into pETCC2 26 (a modified version of pET14b, Novagen) using Nde I and Bam HI or Eco RI sites, to create an in-frame N -terminal hexa-histidine tag. Genes encoding fusions between the catalytic and cofactor-recycling domains (GlpK Tk -AceK M s and G3PD Ec -NOX Ca ) were synthesized.…”
Section: On-line Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior comparison of enzymes that could be used for the first two steps of the model synthesis 18 had suggested that the most suitable enzymes for glycerol phosphorylation were a Thermococcus kodakarensis glycerol kinase (GlpKTk) and a Mycobacterium smegmatis acetate kinase (AceKMs). For the NAD + -dependent production of DHAP from glycerol-3-phosphate (G3P), E. coli glycerol-3phosphate dehydrogenase (G3PDEc) and the water-forming NADH oxidase from Clostridium aminovalericum (NOXCa) were selected.…”
Section: Assembling the Nanomachinesmentioning
confidence: 99%
“…Starting from glycerol and pyrophosphate, a 57% yield of 5-deoxy-5-ethyl-D-xylulose was obtained from l-glycerol-3-phosphate. In another study, the conversion of glycerol to dihydroxyacetone phosphate (DHAP) was reported with a one-pot four-enzyme cascade composed of glycerol kinase (Thermococcus kodakarensis), acetate kinase (Mycobacterium smegmatis), glycerophosphate oxidase (Mycoplasma gallisepticum) and catalase (Micrococcus lysodeikticus) (Hartley et al, 2017). The cascade achieved 88% conversion of glycerol to DHAP in 1 h at 22 • C. The pathway was coupled with a DHAP-dependent fructose-1,6biphosphate aldolase enzyme from Staphylococcus carnosus to produce the rare chiral sugars D-fructose-1,6-biphosphate (3S, 4R) and 3,4-dihydroxyhexulose phosphate (3S, 4R).…”
Section: Substrates For Biomass Transformationmentioning
confidence: 99%